3D Aluminum Hybrid Plasmonic Nanostructures with Large Areas of Dense Hot Spots and Long‐Term Stability. (16th January 2017) - Li, Xi‐Mei; Bi, Ming‐Hai; Cui, Lan; Zhou, Yu‐Zhu; Du, Xi‐Wen; Qiao, Shi‐Zhang; Yang, Jing
Abstract : Plasmonic materials possessing dense hot spots with high field enhancement over a large area are highly desirable for ultrasensitive biochemical sensing and efficient solar energy conversion; particularly those based on low‐cost noncoinage metals with high natural abundance are of considerable practical significance. Here, 3D aluminum hybrid nanostructures (3D‐Al‐HNSs) with high density of plasmonic hot spots across a large scale are fabricated via a highly efficient and scalable nonlithographic method, i.e., millisecond‐laser‐direct‐writing in liquid nitrogen. The nanosized alumina interlayer induces intense and dual plasmonic resonance couplings between adjacent Al nanoparticles with bimodal size distribution within each of the hybrid assemblies, leading to remarkably elevated localized electric fields (or hot spots) accessible to the analytes or reactants. The 3D‐stacked nanostructure substantially raises the hot spot density, giving rise to plasmon‐enhanced light harvesting from deep UV to the visible, strong enhancement of Raman signals, and a very low limit of detection outperforming reported Al nanostructures, and even comparable to the noble metals. Combined with the long‐term stability and good reproducibility, the 3D‐Al‐HNSs hold promise as a robust low‐cost plasmonic material for applications in plasmon‐enhanced spectroscopic sensing and light harvesting. Abstract : 3D Al hybrid plasmonic nanostructures over a large area are fabricated via a simple and highly efficient approach. The nanoscale alumina interlayer and 3D‐stacked nanostructure create dense hot spots with high field enhancements, leading to strong plasmon‐enhanced light harvesting and surface‐enhanced Raman spectroscopy performance comparable to the noble metals for non‐resonant molecules.